2023
DOI: 10.3390/nu15102351
|View full text |Cite
|
Sign up to set email alerts
|

Umbelliferone Ameliorates Memory Impairment and Enhances Hippocampal Synaptic Plasticity in Scopolamine-Induced Rat Model

Ga-Young Choi,
Hyun-Bum Kim,
Jae-Min Cho
et al.

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disorder, characterized by memory loss and cognitive decline. Among the suggested pathogenic mechanisms of AD, the cholinergic hypothesis proposes that AD symptoms are a result of reduced synthesis of acetylcholine (ACh). A non-selective antagonist of the muscarinic ACh receptor, scopolamine (SCOP) induced cognitive impairment in rodents. Umbelliferone (UMB) is a Apiaceae-family-derived 7-hydeoxycoumarin known for its antioxidant, anti-tumor, anticancer, anti-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…36 The increased expression of BDNF, TrkB, the pCREB/CREB ratio, and the inhibition of acetylcholinesterase activity were associated with cognitive improvements. 37 It was reported that about the interrelationships between BDNF and NPW, BDNF could modulate the expression of NPW in neuronal cells via the PI3K/Akt pathway and the application of exogenous BDNF to mice increased synthesis of NPW and also CRH levels in the hypothalamus. 38 NPW participates in the neuroendocrine regulation of pituitary hormone production and may have a significant role in the hypothalamic organization of the endocrine response to stress.…”
Section: Discussionmentioning
confidence: 99%
“…36 The increased expression of BDNF, TrkB, the pCREB/CREB ratio, and the inhibition of acetylcholinesterase activity were associated with cognitive improvements. 37 It was reported that about the interrelationships between BDNF and NPW, BDNF could modulate the expression of NPW in neuronal cells via the PI3K/Akt pathway and the application of exogenous BDNF to mice increased synthesis of NPW and also CRH levels in the hypothalamus. 38 NPW participates in the neuroendocrine regulation of pituitary hormone production and may have a significant role in the hypothalamic organization of the endocrine response to stress.…”
Section: Discussionmentioning
confidence: 99%